ANALISIS PERFORMANCE CASUAL WORKER WAREHOUSE DI PERUM BULOG SUB DIVRE SURAKARTA - Samsoel Bahry; Rochmi Widayanti; Ratna Damayanti (JURNAL ILMIAH EDUNOMIKA, 2019)
Casual workers, better known as freelance workers, are human resources that have special specifications using body power possessed by Public Corporation of BULOG as a loading and unloading force of commodity goods, as well as processing units of food commodities in warehouses. This research is included in a quantitative descriptive study with a population of casual worker warehouses totaling 230 people in this study taken 50% as a source of data as many as 115 people. The data used in this study is primary data with a questionnaire method for respondents. Data is processed using IBM SPSS Statistics 17 multiple linear test. Based on the results of multiple linear regression tests, it shows that Job Training, Work Environment and Work Compensation partially influence the performance of casual worker warehouses at the Sub-Division of Regional Division of Surakarta. While the work discipline partially does not affect the performance of casual worker warehouses at the Sub Division of Surakarta Regional Office of Logistics, which is indicated by the significance of job training 0.002